Sheep Rearing as a Profitable Enterprise: A PRA Study of Kantoli Village in Semi-arid Area of Rajasthan - G. L. Bagdi , Raj Kumar , L. R. Gurjar , Rajiv Gulyani; S.M.K. Naqvi (Indian Journal of Extension Education, 2016)
Participatory Rural Appraisal (PRA) study was carried out in village Kantoli located in Malpura tehsil of Tonk district under Sansad Adarsh Gram Yojna in semi-arid area of Rajasthan during July 2015. Farmers’ behaviour towards sheep management technologies and economically viability of sheep rearing enterprise were studied in detail. Study revealed that majority of sheep farmers were adopting vaccinations to protect their sheep from various diseases and they rear sheeps of Kheri breed, but wanted to adopt sheeps of Patanwadi breed. Matrix ranking technique was used to assess the important technologies of sheep rearing as perceived by farmers and also constraints faced by them in this occupation. It was found that majority of farmers were aware of different sheep management technologies. The most needed important technologies were prevention of abortion in sheep, fodder availability for sheep and development of infrastructures such as shed and trough for feed & drinking of water as perceived by sheep farmers. The study also revealed that Kikar (Prosopis juliflora) was very hazardous to sheep. Lack of grazing land, non-availability of drinking water for sheep, Enterotoxaemia (ET) disease and lack of fodder were other serious constraints faced by sheep farmers of Kantoli village in sheep rearing. Cost benefit analysis of sheep rearing was computed based on the data given by sheep farmers and revealed that the sheep rearing is a profitable enterprise. However, by following the sheep rearing technologies, it has the prospect of becoming a very profitable enterprise.